Hepatitis E virus in pigs and the environment: An updated review of public health concerns - Kuldeep Dhama; Mohd. Iqbal Yatoo; Ruchi Tiwari; Muhammad Bilal; Manish Dhawan; Talha B. Emran; Habib K. BinKhalaf; Ali A. Rabaan; Tauseef Ahmad; Hui Jin; Jeehan H. Alestad; Hatem M. Alhani (Narra Sains Indonesia, 2022)
Hepatitis E virus (HEV) is an important public health problem and is responsible for both acute and chronic viral hepatitis. Public health implications of HEV are derived from its transmission route, either water-borne or food-borne, and its zoonotic potential. Not only in developing countries, but HEV cases are also found in a high number in developed countries. The spread of HEV to the environment might pollute surface waters, which could act as the source of infection for both humans and animals. Identification of the virus in animal products suggests the circulation of HEV within water and food chains. High seroprevalence and circulation of HEV in livestock, in particular pigs, as well as in environmental samples warrants further investigation into pig markets. HEV virulence in different environments and meat supply chains could shed light on the possible sources of infection in humans and the degree of occupational risk. The purpose of this review is to discuss HEV infections with an emphasis on livestock- and environment-related risk factors, and food-borne, water-borne, and zoonotic transmissions.